Lower serum LDL-C levels are associated with poor prognosis in severe fever with thrombocytopenia syndrome: a single-center retrospective cohort study - Guo, Shuai; Dong, Qing; Zhang, Maomei; Tu, Lirui; Yan, Yunjun; Guo, Shougang (Frontiers in Microbiology, 2024)
Background: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease triggered by a novel bunyavirus (SFTSV). Characterized by fever, thrombocytopenia, leukocytopenia, and multiple organ dysfunction manifestations, its primary mode of transmission is through tick bites. Despite the critical role of lipid metabolism in viral infections, the role of lipids in SFTS remains unclear. Methods: This retrospective study analyzed 602 patients with SFTS treated at Shandong Public Health Clinical Center from January 2021 to December 2023. Based on the endpoint events, patients were classified into survival (S) and death (D) groups. The S group was further classified into non-critical (non-C) and critical (C) groups based on symptoms. All patients were followed up for at least 28 days from admission. Propensity score matching, multi-variable logistic regression, survival analysis, time trend analysis, and mediation analysis were conducted to assess the association between LDL-C levels and prognosis in SFTS. Results: Serum LDL-C levels on admission were significantly lower in the D and C groups compared to the S and non-C groups. Logistic regression models indicated a potential association between LDL-C levels and poor prognosis in SFTS. Restricted cubic spline showed a unidirectional trend between LDL-C levels and mortality, with a cutoff value of 1.59 mmol/L. Survival analysis revealed higher and earlier mortality in the low LDL-C group compared to the high LDL-C group. Trends over 28 days post-admission showed that serum LDL-C levels gradually increased in SFTS with a favorable prognosis. Finally, mediation analysis indicated that low LDL-C levels are associated with mortality through poor hepatic, cardiac, and coagulation functions. Conclusion: Low LDL-C levels are potentially associated with poor prognosis in SFTS.